REKONTRUKSI PERAN GURU MELALUI NILAI-NILAI AL-QUR’AN DI ERA MODERN - Fawaid, Ahmad (Fakultas Agama Islam Universitas Islam Madura, 2018)
The teacher’s role of education is very important, because it is the spearhead in improving educations’ Quality, including in the form of students who are intelligent, moral and have a good personality. The teacher must have four basic awareness, namely training pedagogy, professional, personal and social as well as carrying out their duties and functions as educators in accordance the message of Qur'an.